The genus Corvospongilla Annandale, 1911 (Porifera: Demospongiae: Spongillida) from Madagascar freshwater with description of a new species: biogeographic and evolutionary aspects - Manconi, Renata; Pronzato, Roberto (Zootaxa, 2019)
We report here the first record of five genera of Spongillida (Porifera, Demospongiae) in both lentic and lotic water of Madagascar and the discovery of a new species of the genus Corvospongilla from the Betsiboka River hydrographic basin. Corvospongilla lemuriensis sp. n. diverges from all the other known species of the genus in its unique combination of diagnostic morphotraits (a) sessile gemmules with chambered pneumatic layer within tri-layered theca and enveloped by spicular cage of dominant acanthostrongyles, (b) dominant acanthostrongyles and less frequent acanthoxeas-strongyloxeas as megascleres and gemmuloscleres. The new species is characterised by the exclusive presence of a well-developed pneumatic layer in sessile gemmules not described for the genus until now. The new record confirms a Gondwanian track for the genus Corvospongilla and increases the knowledge on Spongillida historical biogeography. In synthesis the present discovery of Corvospongilla in the Malagasy biogeographic province (a) contributes to the assessment of Afrotropical biodiversity, (b) enlarges the geographic range of the genus reducing its disjunct distribution, and (c) focus on the evolutionary history of adaptive morphofunctional traits of resting bodies and life cycle timing in ephemeral water of the south-eastern Austral hemisphere.